(untitled) (Journal of Health, Population and Nutrition, 2009)
To facilitate the assessment of the safety profile of rotavirus vaccines effectively, baseline data on intussusception are important for comparison with intussusception rates following the introduction of vaccine. The aim of the study was to describe epidemiological and clinical features of intussusception in children aged less than five years in an Indian medical facility. Hospital data on intussusception for children discharged during 1 January 2001-30 June 2004 from the Christian Medical College Hospital, Vellore, India, were reviewed. Relevant information was extracted from medical records to classify cases according to the criteria of the Brighton Collaboration Intussusception Working Group. Complete review of medical records for clinical and demographic information was only performed for those cases fulfilling level 1 diagnostic certainty (definite intussusception) (Study ID 101245). During the surveillance period, 31 infants and children with definite intussusception were identified. The majority (61.2%) of the cases occurred in the first year of life. The male : female ratio was 3.4 : 1. Intussusception cases occurred round the year with no distinct seasonality. No intussusception-associated death was recorded. This study provides baseline data on intussusception in South India. Cases identified in the study were similar in presentation and demographics as those observed in other Asian settings. Prospective surveillance systems, using standardized case definitions will further increase the understanding of the aetiology and epidemiology of intussusception, especially as new rotavirus vaccines are made available. J Health Popul Nutr 2009 Oct; 27(5):660-665